SMALL INTESTINAL TRANSPLANTATION IN HUMANS WITH OR WITHOUT THE COLON, - Todo, Satoru (1994)
Under FK506-based immunosuppression, 16 cadaveric small bowel transplantations were performed in 15 recipients with (n = 5) or without (n = 11) the large bowel. Twelve (80%) patients are alive after 1.5 to 19 months, 11 bearing their grafts, of which 4 include colon. The actuarial one-year patient and graft survivals are 87.5% and 65.9%, respectively. Five grafts were lost to acute (n = 4) or chronic (n = 1) rejection, and 3 of these patients subsequently died after 376, 440, and 776 days total survival. Six recipients developed severe CMV infection that was strongly associated with seronegative status preoperatively and receipt of grafts from CMV positive donors; 3 died, and the other 3 required prolonged hospitalization. Currently, 9 patients are free from TPN 1–18 months postoperatively, 2 require partial TPN, and one has returned to TPN after graft removal. The results show the feasibility of small bowel transplantation but emphasize the difficulty of managing these recipients not only early but long after their operation.